Drug-Induced Liver Injury: An Institutional Case Series and Review of Literature. (12th March 2018) - Gayam, Vijay; Khalid, Mazin; Shrestha, Binav; Hossain, Muhammad Rajib; Dahal, Sumit; Garlapati, Pavani; Gill, Arshpal; Mandal, Amrendra Kumar; Sangha, Ruby
Drug-induced liver injury (DILI) is the most common cause of acute liver failure in the USA. DILI can be broadly classified as Intrinsic and Idiosyncratic. Identifying predictors and at-risk patients are challenging but can have a substantial clinical implication. This case report series demonstrates the importance of valproic acid, fluconazole, and amiodarone as potential hepatoxic agents of drug-induced liver injury leading to acute hepatic failure. The causality in all cases was established by Roussel Uclaf Causality Assessment Method/Council for International Organizations of Medical Sciences score and Naranjo Algorithm. Obesity, hypo-perfusion state, and concurrent hepatotoxic agent might identify at-risk patients. Further studies are required to understand the risk factors.